2019
DOI: 10.1097/md.0000000000017922
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of HT048 and HT077 for body fat and weight loss in overweight adults

Abstract: Background:The prevalence of excessive body weight has rapidly increased worldwide over the past decades; however, medications are intended for moderately and severely obese patients and are associated with side effects. As an alternative approach, the use of traditional herbal medicines has gained increasing popularity among overweight individuals in recent years in East Asia. HT048 is an herbal extract of Citrus unshiu and Crataegus pinnatifida, and HT077 is an herbal extract of Nelumbo nucifera and Prunus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…1.4; issue date, 2019) was approved by the Institutional Review Board of Semyung University Korean Medicine Hospital (approval no. SMJOH-2019-09-01) and registered at the Korean Clinical Research Information Service (KCT0005546).We followed the methods of Song et al 2019 [ 5 ]. The participants fulfilled all the criteria mentioned in suppl.…”
Section: Methods and Designmentioning
confidence: 99%
“…1.4; issue date, 2019) was approved by the Institutional Review Board of Semyung University Korean Medicine Hospital (approval no. SMJOH-2019-09-01) and registered at the Korean Clinical Research Information Service (KCT0005546).We followed the methods of Song et al 2019 [ 5 ]. The participants fulfilled all the criteria mentioned in suppl.…”
Section: Methods and Designmentioning
confidence: 99%
“…Only in the case of a medical emergency, the individual’s randomization code and group allocation can be identified as described previously. 29 …”
Section: Methods and Designmentioning
confidence: 99%
“…Many clinical trials have reported different health-promoting activities for hawthorn [148][149][150][151][152][153][154]. In a study on 2681 patients suffering from congestive heart failure, the administration of hawthorn extract (900 mg/day) for 620 days reduced the odds ratio of sudden cardiac death in patients with lower left ventricular function [155].…”
Section: Health-promoting Activities Of Hawthorn Reported In Clinicalmentioning
confidence: 99%